From Experience to E-WOM: Unpacking the Power of Tourist Motivation and Marketing Mix on Revisit Intentions in Taiwan - Tiong, Piter; Farida, Umi; Haris, Abdul; Azizurrohman, Muhammad (Journal of Marketing Innovation (JMI), 2025)
This study investigates the mediating role of electronic word-of-mouth (e-WOM) between the marketing mix, tourist experience, and revisit intentions, and examines how tourist motivation moderates the e-WOM–revisit intention relationship. Data from 300 tourists who had recently visited Taiwan were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that e-WOM significantly mediates the relationship between both the marketing mix and tourist experience on revisit intentions. A well-executed marketing mix and positive experiences encourage tourists to share their experiences online, which increases their likelihood of revisiting. The moderating analysis reveals that the influence of e-WOM on revisit intentions is stronger for tourists seeking personal enjoyment compared to transactional motives. This study contributes to consumer behavior theory by highlighting how intrinsic motivations amplify the impact of e-WOM. Practically, it offers strategies for fostering e-WOM through personalized experiences, social media engagement, and emerging technologies like AI and augmented reality. Future research should adopt longitudinal designs to capture evolving tourist behavior and explore the role of social media influencers on platforms such as TikTok. The findings underscore the importance of e-WOM in shaping tourist behavior, offering practical insights for destination marketers to enhance engagement and revisit intentions.